Linking Environmental Performance, Disclosure, and ISO 14001 to Firm Financial Success - Dede Sunaryo (Universitas Muhammadiyah Tangerang, 2026)
This study aims to analyze the influence of environmental performance, environmental disclosure, and ISO 14001 certification on corporate financial performance. Sustainability and environmental responsibility have become critical factors in modern business strategies, yet the relationship between environmental initiatives and financial outcomes remains debated in academic literature. Environmental performance is measured using PROPER, disclosure through the GRI index, and ISO 14001 with a dummy variable for certified firms, while financial performance is assessed using accounting indicators (ROA, ROE). The findings reveal that: (1) environmental performance has a significant positive effect on financial performance, with stronger impacts on market-based indicators than accounting measures; (2) environmental disclosure positively influences financial performance, particularly in highly visible firms; (3) ISO 14001 certification contributes positively to long-term financial performance despite short-term implementation costs; and (4) synergistic effects emerge when all three environmental variables are applied simultaneously. The novelty of this research lies in integrating three key environmental dimensions performance, disclosure, and certification within a single framework to evaluate their combined and interactive effects on financial outcomes. This study contributes to the literature by providing empirical evidence from the Indonesian context, highlighting how sustainability initiatives not only enhance legitimacy but also strengthen market trust and long-term corporate value.